Behaviour of CFRP-confined concrete-filled circular steel tube stub columns under axial loading. (April 2018) - Ding, Fa-xing; Lu, De-ren; Bai, Yu; Gong, Yong-zhi; Yu, Zhi-wu; Ni, Ming; Li, Wei
Abstract: This paper presents an experimental and theoretical study of CFRP-confined concrete-filled circular steel tube (CFT) stub columns, which aims at investigating the effects of different numbers of CFRP layers and concrete strengths on the mechanical performance of CFRP-confined CFT stub columns. Based on continuum mechanics, a mechanical model of concentric cylinder consisting of CFRP, circular steel tube and concrete core under concentric loading was established and the corresponding elasto-plastic methods were obtained through a FORTRAN program. The influence of the number of CFRP layers on the ultimatecapacity, ductility and confinement effect of the steel tube on the core concrete wasdiscussed and identified. Finally, based on the limit equilibrium and elasto-plastic methods, a simplified formula for the ultimatecapacity of CFRP-confined CFT stub columns was proposed. Good agreement of the ultimate capacity was found between the elasto-plastic methods and the proposed formula, with the maximum discrepancy less than 12%.